Renewable Energy Progress in The European Union Under the Challenges Brought by The Russian-Ukrainian War - Andreea - Emanuela DRĂGOI; Paul CALANTER; Cornelia NEAGU; Daniela ZISU (Communications of International Proceedings, 2024)
The ongoing Russian - Ukrainian war followed by the energy crisis that emerged in mid-2022 have sparked concern about the European Union’s security energy security, highlighting that renewable energy must be at the core of European energy policy in the medium and long term. Our paper aims to investigate the main drivers and progresses of renewable energy (RE) development in the European Union (EU) using a quantitative analysis, based on the latest Eurostat data, to show what Member States perform best in the European hierarchy. Our research also aims to highlight the existing opportunities and threats for RE development in the Member States under the green transition goals. Our main finding is that while there are significant progresses toward boosting RE development and use in most Member States, additional national policies focused on incentives and special derogations for investors may be necessary to further develop RE across EU. Our second finding is that, under the current geopolitical framework, RE remains an essential pillar for reducing EU’s dependence on fossil fuels imported from Russian Federation.
Keywords: Renewable energy; Green transition; Russian - Ukrainian war; EU’s energy mix; EU’s energy security